Multi-Objective Photovoltaic Planning in Active Distribution Networks Considering Voltage Stability Margin - Trieu Ngoc Ton (PT FORMOSA CENDEKIA GLOBAL, 2026)
The increasing integration of photovoltaic (PV) generation into active distribution networks (ADNs) necessitates planning strategies that simultaneously improve network efficiency and operational security. Existing PV planning methods primarily focus on power loss reduction and voltage regulation, while voltage stability is often neglected during optimization. This paper proposes a multi-objective PV planning framework based on the Multi-Verse Optimizer (MVO) to determine the optimal locations and capacities of PV units by minimizing normalized active power loss and voltage deviation while maximizing the voltage stability margin (VSM). The proposed framework is integrated with the Backward/Forward Sweep load-flow algorithm (BFS) and validated on the 33-bus and 69-bus distribution systems. Simulation results show that the proposed method reduces active power loss from 202.67 kW to 67.58 kW and increases the minimum bus voltage from 0.9131 p.u. to 0.9784 p.u. for the 33-bus system. For the 69-bus system, power loss is reduced from 224.98 kW to 72.43 kW, while the minimum bus voltage improves from 0.9092 p.u. to 0.9802 p.u. The proposed framework also achieves the highest voltage stability margin and the fastest convergence compared with PSO, GWO, HHO, and MPA, demonstrating its effectiveness for PV planning in renewable-rich distribution networks.